2011
DOI: 10.1007/s11033-011-1423-9
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean

Abstract: Northeast of China is the main soybean production area, drought and low-temperature tolerance are both main factors involved in reducing soybean yield and limiting planting regions, the most effective way to solve this problem is to breed cultivars with drought and low-temperature tolerance. A set of the BC(2)F(3) lines was constructed with Hongfeng 11 as recurrent parent and Harosoy as donor parent, and screened in drought and low-temperature condition at the germination stage. Related QTLs were obtained by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…Several studies have indicated that mapping QTL with BC populations was more time‐ and cost‐effective than conventional QTL mapping (Zhang et al. , Wang et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have indicated that mapping QTL with BC populations was more time‐ and cost‐effective than conventional QTL mapping (Zhang et al. , Wang et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these two BC populations could also be used for mapping QTL for other agronomic traits. Several studies have indicated that mapping QTL with BC populations was more time-and cost-effective than conventional QTL mapping (Zhang et al 2012, Wang et al 2013. It was because BC populations have lower genetic background noise than other populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that stresses co-exist under certain natural environments, further makes it harder to improve rice yield. For instance, drought and low temperature in the northern hemisphere (Zhang et al, 2012), cold-dry temperatures in the highland plains, and higher relative humidity and cloudy nights in the coastal regions co-exist. But also, during the course of drought stress development, pathogens can infect plants or drought stress can occur on already pathogen infected plants.…”
Section: Introductionmentioning
confidence: 99%